In Praise of Uncertainty, Ambiguity and Wonder - White, Boyd Eric (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
This article takes its direction from notable educators such as John Dewey and Elliot Eisner who argue in favour of endorsing uncertainty and related responses within educational practice. The argument is a push-back against current emphasis on standardization, with its accompanying focus on single right answers that don’t do justice to the complexities inherent in our daily lives. The dual nature of uncertainty is exemplified in the depiction of one person’s interactions with two famous paintings. To provide the reader with a parallel encounter with uncertainty, the article includes a short video and concludes with an ekphrastic poem in response to the video, to illustrate the points being made.